Assistancing of posyandu cadres in monitoring the growth of infants aged 0-59 months - Entoh, Christina; Sitorus, Sony Bernike Magdalena; Siregar, Nilda Yulita (Community Empowerment)
One of the government's efforts in empowering the community to reduce infant and under-five mortality rates, and improve health status in the community is to optimize the role of cadres in society. Thus, it is necessary to have activities that can increase the knowledge, attitudes and actions of cadres in monitoring infant growth, especially in filling out the Towards Healthy Card (KMS) chart. The purpose of this community service activity is to increase the knowledge, attitudes, and actions of cadres in filling out KMS charts for early detection of malnutrition and stunting. The target of this community service activity was posyandu cadres in the Kayamanya Health Center Work Area, Poso Kota District. The service method was carried out in several stages (1) pre-test before mentoring; (2) presentation of material on anthropometric measurements and filling out KMS charts; (3) exercise and practice of anthropometric measurements and chart filling; and (4) post-test after mentoring. This activity resulted in an increase in the average score of knowledge, attitudes and actions of cadres after being given assistance to cadres.